Analysis Of Depression And Psychosocial Problems Elderly In The Nursing Homes - Syarniah, Syarniah; Rachmadi, Agus; Ilmi, Bahrul (Poltekkes Kemenkes Banjarmasin, 2024)
Progress in the fields of helath and technology as well as increasing welfare of course also have an impact on individual health. The healthier the individual, the greater the opportunity to increase his or her lufespan.Thus the number or erderly individuals also continues to increase.Erderly are individuals who are 60 years old or more.The elderly physioligical systems have experienced a decline.This condition certainly has the impact that elderly, so they have various diseases that are classified as degenerative diseases such as hypertension, diabetes mellitus, osteoarthritis and others. Most elderly are also unable to be economically productive. Elderly have not income and no adequate family support can live in nursing home. Nursing home is social or free of charge residence for elderly poors. Conditions of being economically disadvantaged, having physical illness, no family support, and have to live in a nursing home can trigger elderly to experience health problems such as depression. Depression in the elderly has the impact of psychosocial problems such as powerlesness, hopelessness, low self-esteem, and social isolation. The aim of this research is to analyze depression and psychosocial problems in elderly living in nursing homes. The research design descriptive analytic. The research sample was elderly living in nursing homes and sampling technique used was purposive sampling. The total sample was 86 elderly. Data collection used the Geritriac Depression Scale instrument and psychosocial response instruments. Descriptive data analysis. The research results showed that 87% of the 86 respondents experienced depression. In 75 elderly who were depressed, it was found that 97% (73 people) experienced psychosocial problems low self-esteem, 93% (70 people) of powerlesness, 99% (74 people) of hopelessness, and 77% (58 people) of social isolation. The suggestions given are strengthening care, especially related to the mental health of the elderly and the need for programmed activities that support the physical, psychological, socio-cultural and spiritual health of the elderly living in nursing homes. Keywords: Depression, Psychosocial Problems, Elderly.